2009
DOI: 10.1007/s00384-009-0787-y
|View full text |Cite
|
Sign up to set email alerts
|

MICB0106 gene polymorphism is associated with ulcerative colitis in central China

Abstract: BackgroundThe highly polymorphic nonclassical MHC class I chain-related genes A and B (MICA and MICB) encode stress-inducible glycoproteins expressed on various epithelial cells including intestinal epithelial cells. MICA and MICB gene polymorphisms and expressions are associated with autoimmune diseases but not known in ulcerative colitis (UC).AimsTo investigate the association of MICB exon 2-4 polymorphisms and soluble MICA (sMICA) expression with the susceptibility of UC in central China.Materials and metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 39 publications
0
14
1
Order By: Relevance
“…However, several studies of the MICB locus have shown positive disease associations. MICB*008 was linked to Crohn's disease in a Spanish population (17) and was positively associated with ulcerative colitis in a central Chinese population (19). In addition, MICB*004 was reported to be associated with multiple sclerosis and rheumatoid arthritis in a Spanish population (13, 16), and MICB*005:02 was negatively associated with cervical cancer in northeastern Thai women (20).…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies of the MICB locus have shown positive disease associations. MICB*008 was linked to Crohn's disease in a Spanish population (17) and was positively associated with ulcerative colitis in a central Chinese population (19). In addition, MICB*004 was reported to be associated with multiple sclerosis and rheumatoid arthritis in a Spanish population (13, 16), and MICB*005:02 was negatively associated with cervical cancer in northeastern Thai women (20).…”
Section: Discussionmentioning
confidence: 99%
“…Past reports on the allelic distribution of MICB were of little information with regard to disease. A growing body of research now shows that MICB polymorphism is related to certain diseases . However, as HLA‐MICB‐MICA haplotypes have been reported in different people , this disease association may be secondary and due to LD with HLA alleles.…”
Section: Mica Allele Frequencies In Hainan LI Populationmentioning
confidence: 99%
“…For example, specific MICA alleles are overrepresented in rheumatoid arthritis, inflammatory bowel disease and type 1 diabetes patients, implicating a role in disease pathogenesis (24,25). Likewise, MICB polymorphisms are also associated with celiac disease, ulcerative colitis, and multiple sclerosis (26–28).…”
Section: Chromosome 6q251 (Ulbp6/ulbp3)mentioning
confidence: 99%